2017
DOI: 10.1002/2017ja023968
|View full text |Cite
|
Sign up to set email alerts
|

Global equatorial plasma bubble growth rates using ionosphere data assimilation

Abstract: Flux tube integrated Rayleigh‐Taylor instability growth rates computed by using the results of ionosphere data assimilation are used for the first time to investigate global plasma bubble occurrence. The study is carried out by assimilating total electron content measurements using ground‐based Global Positioning System (GPS) receivers into thermosphere ionosphere electrodynamic general circulation model, and the growth rates are calculated by using standalone model run without assimilation (control run) as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 45 publications
(61 reference statements)
0
24
0
Order By: Relevance
“…Rajesh et al . [] demonstrated that the global RTI growth rates calculated using their data assimilation results agree well with corresponding ROTI values during both quiet and disturbed conditions.…”
Section: Plasma Bubble Inhibition Over Taiwanmentioning
confidence: 74%
See 4 more Smart Citations
“…Rajesh et al . [] demonstrated that the global RTI growth rates calculated using their data assimilation results agree well with corresponding ROTI values during both quiet and disturbed conditions.…”
Section: Plasma Bubble Inhibition Over Taiwanmentioning
confidence: 74%
“…Though the observations reveal intense bubble activity on all these nights, no EPB was observed over Taiwan on the night of 17 March 2015, when the St. Patrick's Day storm occurred [ Rajesh et al . [, Figure 3 (bottom panel)]].…”
Section: Plasma Bubble Inhibition Over Taiwanmentioning
confidence: 99%
See 3 more Smart Citations